The Bane of Fairness - Lauretani, Aaron (The Oracle, 2021)
What is pertinent for the purposes of this paper is to confront the very issue of how, in my estimation, capitalism betrays Rawls’ mission to establish a conception of an equal and sustainable political society. An important component of Rawls’ vision is a society in which people are given the capacity to meaningfully participate together; provided with real opportunities to enter privileged and influential institutions and alter the course of their political lives. Beyond each person being able to pursue their individual vision of a good life, Rawls also recognizes the importance of a society that maintains its cohesion. By drawing one’s attention first and foremost to Marx’s theory of the forms of alienation, I shall reveal the extent to which capitalism compromises the capacity of each person to be equal in the way Rawls defines. Furthermore, while remaining indebted to the genius of Marx, I will also draw upon the important work of Charles Taylor’s communitarian argument to articulate the manner in which Rawls’ conception of a political society is not stable long-term. Thus, it will be shown that Rawls’ conception of fairness as it pertains to equality and sustainability is incompatible with the capitalism his theory allows.